PENGEMBANGAN INSTRUMEN KECERDASAN NUMERIK SISWA SMP - NUR ALAMSYAH (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2023)
This research is a development research carried out in order to produce instruments that can be used to determine the numerical abilities of students of Cibarusah Middle School 2 Negri. Numerical ability instruments are arranged based on the dimensions and indicators of numerical abilities which consist of mathematical calculations, logical thinking, problem solving, and recognizing numerical patterns and their relationships while the mathematics learning outcomes instruments are arranged based on basic competencies and indicators related to data processing material . The instrument is presented in the form of an ordinary multiple choice test totaling 30 questions with 4 answer choices. Instrument development testing includes the stages of needs analysis, theoretical analysis, compiling grids, implementing grids into items, validation tests, reliability tests, and difficulty levels. The results of this study indicate that all items on the numerical ability instrument have validity with a criterion value or r table of 0.374, a significant level of ? = 0.01 and high reliability with a reliability coefficient value of 0.901. ABSTRAKPenelitian ini merupakan penelitian pengembangan yang dilakukan guna menghasilkan instrumen yang dapat digunakan untuk mengetahui kemampuan numerik siswa Sekolah Menengah Pertama. Instrumen kemampuan numerik disusun berdasarkan dimensi serta indikator kemampuan numerik yang terdiri dari perhitungan secara matematis, berpikir logis, pemecahan masalah, dan mengenali pola-pola numerik serta hubungan-hubungannya sedangkan instrumen hasil belajar matematika disusun berdasarkan kompetensi dasar dan indikator yang berkaitan dengan materi pengolahan data. Instrumen disajikan dalam bentuk tes pilihan ganda biasa berjumlah 30 butir soal dengan 4 pilihan jawaban. Uji coba pengembangan instrumen mencakup tahapan analisis kebutuhan, analisis teoritik, menyusun kisi-kisi, mengimplementasikan kisi-kisi menjadi butir soal, uji validasi, uji reliabilitas, dan tingkat kesukaran. Hasil penelitian ini menunjukkan bahwa seluruh butir soal pada instrumen kemampuan numerik memiliki validitas dengan besarnya nilai kriteria atau r tabel sebesar 0,374 taraf signifikan ? = 0,01 dan reliabilitas yang tinggi dengan nilai koefisien reliabilitas sebesar 0,901.